Systematic literature review: future skills of teachers - Shamsidar Zainor, Nor; Hamzah, Mohd Isa; Zulkifli, Hafizhah (International Journal of Evaluation and Research in Education (IJERE), 2025)
This systematic literature review (SLR) investigates the essential skills future teachers require to succeed in a rapidly evolving educational landscape, influenced by technological advancements and shifting pedagogical paradigms. It highlights the misalignment between the skills possessed by teachers and the demands of 21st-century education, which can result in teaching becoming irrelevant. Employing a qualitative approach in accordance with preferred reporting items for systematic reviews and meta-analyses (PRISMA) standards, this study analyzed two primary databases—Web of Science (WoS) and Scopus—alongside Google Scholar, focusing on empirical journal articles published in either Malay or English from 2019 to 2023. From an initial pool of 55,362 articles, only 14 were selected for analysis. The qualitative findings identified four key themes: i) digital technology skills; ii) communication skills; iii) lifelong learning skills; and iv) socioemotional skills. These insights emphasize the urgent need for teacher training programs to integrate these competencies into their curricula. By addressing these gaps, educational stakeholders can better equip teachers to meet the demands of 21st-century classrooms, ultimately enhancing educational outcomes and fostering student success. Future research should further assess the effectiveness of these training programs on teaching performance and student achievement.